The Fruit of Contradiction: Reading Durian through a Cultural Phytosemiotic Lens - John Charles Ryan (Philosophies, 2024)
Distinctive for its pungent and oftentimes rotten odor, the thorny fruit of durian (Durio spp.) is considered a delicacy throughout Asia. Despite its burgeoning global recognition, durian remains a fruit of contradiction—desirable to some yet repulsive to others. Although regarded commonly as immobile, mute, and insentient, plants such as durian communicate within their own bodies, between the same and different species, and between themselves and other life forms. As individuals and collectives, plants develop modes of language—or phytodialects—that are specific to certain contexts. Focused on vegetal semiosis or sign processes, a phytosemiotic lens views plants as dynamic and expressive subjects positioned within lifeworlds. Absent from phytosemiotic theory, however, are the cultural sign processes that take place within and between plants—what I call cultural phytosemiotics. The framework I propose calls attention to the interlinked biological, ecological, and cultural dimensions of signification between plants and non-plants. From a phytosemiotic standpoint, this article examines historical, cinematographic, and literary narratives of durian. Reflecting the fruit’s divisive sensory effects, historical accounts of Durio by Niccolò de’ Conti, Jan Huyghen van Linschoten, Georg Eberhard Rumphius, and William Marsden alternate between praise and disdain. Moreover, films such as Fruit Chan’s Durian Durian (2000) and Anthony Chen’s Wet Season (2019) narrativize the polarities that similarly figure into historical depictions of the species. Literary narratives, including the poems “Durians” (2005) by Hsien Min Toh and “Hurling a Durian” (2013) by Sally Wen Mao, investigate the language of durian’s olfactory and gustatory sensations. Along a continuum between adoration to revulsion, durian embodies the otherness of vegetal being. In an era of rampant biodiversity loss, learning to embrace botanical difference should be a human imperative.